Production of Pacific whiteleg shrimp, Litopenaeus vannamei through implementation of rapid biofloc technology - Kasan, N A; Kamaruzzan, A S; Rahim, A I A; Ishak, A N; Jauhari, I; Ikhwanuddin, M (IOP conference series. Earth and environmental science, 2019)
A green technology known as rapid biofloc was implemented to reduce environmental damage while improving production of Pacific whiteleg shrimp, Litopenaeus vannamei to meet global market demand. Since there was no intensive application of biofloc technology being implemented at an industrial scale, this study aimed to assess the effect of biofloc in order to optimize water quality and maximize overall shrimp production. To speed-up the development of biofloc in L. vannamei cultures, an isolated biofloc boost-up bacteria inoculum was added during a new shrimp post-larvae (PL) stocking program. Samples of water, shrimp and biofloc were collected at ten day intervals from the new stocking of shrimp PL until harvest time (±100 days). Biofloc was observed starting to form as early as 10 days after shrimp the cultivation period began, and biofloc formation was speeded up by the addition of the inoculum. The biofloc effectively enhanced good water quality which resulted in an increase in shrimp biomass. The rapid biofloc formation and aggregation of beneficial microbes in the biofloc were responsible for maintaining good water quality and optimizing shrimp survival and production. Therefore, knowledge on the microbial composition in biofloc is deemed important for the successful design and application of biofloc technology to support a sustainable shrimp aquaculture industry.